Trust After Terror: Institutional Trust Among Young Terror Survivors and Their Parents After the 22nd of July Terrorist Attack on Utøya Island, Norway - Nilsen, Lisa Govasli; Thoresen, Siri; Wentzel-Larsen, Tore; Dyb, Grete (Frontiers in Psychology, 2019)
In the aftermath of terrorist attacks and disasters, public institutions play an important role in re-establishing safety and justice. However, little is known about the importance of institutional trust for victims’ potential for healing in the aftermath of mass trauma. This study examines levels of post-terror trust in the police and in the justice system among young survivors from the 2011 Utøya terror attack and their parents. Furthermore, it investigates how institutional trust develops over time among directly affected populations, and whether it is associated with psychological distress. 325 survivors and 463 parents were interviewed face-to-face at wave one (4-5 months post-terror) and 285 survivors and 435 parents at wave two (14-15 months). Levels of institutional trust in victims were compared to general population data from the European Social Survey adjusted for age, gender and ethnic background. Measures included trust in the police and justice system, post-traumatic stress reactions, anxiety and depression, and quality of life. Trust in the police among survivors and parents was higher than or comparable to trust levels in the general population at wave one, but decreased for survivors and parents at wave two. Trust in the justice system was higher among those directly affected than in the general population, and increased from wave one to wave two. Levels of institutional trust were negatively associated with distress for survivors in both waves and for parents in wave two. Levels of institutional trust were positively associated with perceived quality of life in parents and survivors. Directly affected groups’ institutional trust differed from that of the general population following the terrorist attack, although being directly affected did not necessarily imply weakened institutional trust. This study found trust to be institution specific, however, trust in institutions changed with time, and the passing of time might be an important factor in better understanding whether trust will generalize across institutions or not. Institutional trust was negatively associated with psychological distress. This finding highlights the potential for institutions to create a healing post-disaster environment.